Altered glucose kinetics occurs with aging: a new outlook on metabolic flexibility - Curl, Casey C.; Leija, Robert G.; Arevalo, Jose A.; Osmond, Adam D.; Duong, Justin J.; Huie, Melvin J.; Masharani, Umesh; Horning, Michael A.; Brooks, George A. (American journal of physiology: endocrinology and metabolism, 2024)
To determine metabolic flexibility in response to an OGTT, we studied healthy young and older men and women to determine glucose kinetics and changes in RER. Compared to young subjects, glucose kinetics were suppressed in older healthy individuals during an OGTT. Surprisingly, the age-related changes in glucose flux were not reflected in RER measurements; thus, RER measurements do not give a complete view of metabolic flexibility in healthy individuals. Our purpose was to determine how age affects metabolic flexibility and underlying glucose kinetics in healthy young and older adults. Therefore, glucose and lactate tracers along with pulmonary gas exchange data were used to determine glucose kinetics and respiratory exchange ratios [RER = carbon dioxide production (V̇co 2 )/oxygen consumption (V̇o 2 )] during a 2-h 75-g oral glucose tolerance test (OGTT). After an 12-h overnight fast, 28 participants, 15 young (21–35 yr; 7 men and 8 women) and 13 older (60–80 yr; 7 men and 6 women), received venous primed-continuous infusions of [6,6- 2 H]glucose and [3- 13 C]lactate with a [Formula: see text] bolus. After a 90-min metabolic stabilization and tracer equilibration period, volunteers underwent an OGTT. Arterialized glucose concentrations ([glucose]) started to rise 15 min post glucose consumption, peaked at 60 min, and remained elevated. As assessed by rates of appearance (Ra) and disposal (Rd) and metabolic clearance rate (MCR), glucose kinetics were suppressed in older compared to young individuals. As well, unlike in young individuals, fractional gluconeogenesis (fGNG) remained elevated in the older population after the oral glucose challenge. Finally, there were no differences in 12-h fasting baseline or peak RER values following an oral glucose challenge in older compared to young men and women, making RER an incomplete measure of metabolic flexibility in the volunteers we evaluated. Our study revealed that glucose kinetics are significantly altered in a healthy aged population after a glucose challenge. Furthermore, those physiological deficits are not detected from changes in RER during an OGTT. NEW & NOTEWORTHY To determine metabolic flexibility in response to an OGTT, we studied healthy young and older men and women to determine glucose kinetics and changes in RER. Compared to young subjects, glucose kinetics were suppressed in older healthy individuals during an OGTT. Surprisingly, the age-related changes in glucose flux were not reflected in RER measurements; thus, RER measurements do not give a complete view of metabolic flexibility in healthy individuals.